Proceedings of the 2017 ACM Conference on Innovation and Technology in Computer Science Education 2017
DOI: 10.1145/3059009.3059061
|View full text |Cite
|
Sign up to set email alerts
|

Code Quality Issues in Student Programs

Abstract: Because low quality code can cause serious problems in software systems, students learning to program should pay attention to code quality early. Although many studies have investigated mistakes that students make during programming, we do not know much about the quality of their code. This study examines the presence of quality issues related to program ow, choice of programming constructs and functions, clarity of expressions, decomposition and modularization in a large set of student Java programs. We inves… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
70
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(73 citation statements)
references
References 14 publications
2
70
0
1
Order By: Relevance
“…Modularization and decomposition can be caused. If students investigate these faults, timely then can use tools to solve the problem [40].…”
Section: Design Patterns and Quality Assurancesmentioning
confidence: 99%
See 2 more Smart Citations
“…Modularization and decomposition can be caused. If students investigate these faults, timely then can use tools to solve the problem [40].…”
Section: Design Patterns and Quality Assurancesmentioning
confidence: 99%
“…Clear and refactored with clear quality programs are obtained [40] Ana Rodriguez (2017) Mobile rely on batteries and APPS use much battery…”
Section: Functions Clearity Expressions Finding Demoularizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Some educators use static analysis tools such as Checkstyle 1 or FindBugs 2 to support the assessment of programming assignments. For example, Keuning et al [18] recently showed that many student programs in the (huge) Blackbox database contain quality issues as reported by PMD 3 , and that students hardly ever fix an issue, even when they make use of analysis tools. These tools check a large range of potential quality issues, but it is not clear which of these tools are suitable or even appropriate in an educational context.…”
Section: Introductionmentioning
confidence: 99%
“…Some educators use static analysis tools such as Checkstyle 1 or FindBugs 2 to support the assessment of programming assignments. For example, Keuning et al [18] recently showed that many student programs in the (huge) Blackbox database contain quality issues as reported by PMD 3 , and that students hardly ever x an issue, even when they make use of analysis tools. These tools check a large range of potential quality issues, but it is not clear which of these tools are suitable or even appropriate in an educational context.…”
Section: Introductionmentioning
confidence: 99%